THE ROLE OF ISLAMIC LAW IN THE DAKWAH OF HAJJ WORSHIP 2024 - Mohammad Adnan; Alhimaidi Ahmed (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This study explores the integral role of Islamic law (Sharia) in the propagation and practice of Hajj worship in 2024, through the lens of Ushul Fiqh (the principles of Islamic jurisprudence). Hajj, as one of the Five Pillars of Islam, demands meticulous adherence to ritualistic and legal guidelines that are deeply rooted in Islamic law. This research examines how Islamic legal principles shape the understanding, preparation, and execution of Hajj among contemporary Muslim communities. It delves into the jurisprudential foundations that underpin Hajj rituals, highlighting the dynamic interplay between traditional fiqh and modern contexts. Furthermore, the study investigates the educational and missionary aspects of Hajj, emphasizing how legal rulings are communicated and taught to prospective pilgrims. By analyzing recent fatwas, legal discourses, and practical implementations, the paper aims to provide a comprehensive overview of how Ushul Fiqh continues to influence the observance of Hajj in an evolving global landscape. This research not only contributes to a deeper understanding of the doctrinal aspects of Hajj but also offers insights into the broader implications of Islamic jurisprudence in contemporary religious practices.